Proteomic Techniques as Biomarkers for Multiple Sclerosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at the Montreal Neurological Institute and other centers in Canada performed proteomics screening of CSF samples collected from 19 children at presentation of acquired inflammatory CNS demyelinating syndromes.